Mechanical Characterization and Modeling of Cyclic Behavior of Ultra High Molecular Weight Polyethylene (UHMWPE) - Colak, Ozgen U.; Asmaz, Kerem; Hassan, Tasnim (TRANS TECH PUBLICATIONS LTD, 2012)
The objective of this work is to study the stress-strain responses of ultra high molecular weight polyethylene (UHMWPE) under uniaxial and biaxial cyclic loading through systematically conducting experiments and model simulations. Experiments involved prescribing axial, strain and stress controlled, cycles to the specimens of UHMWPE. Since the ratcheting strain and its accumulation rate are sensitive to the mean (or steady) and amplitude stresses of the prescribed loading cycles, these parameters were varied in the experiments conducted. The viscoplasticity theory based on overstress (VBO) [1] was implemented to simulate the cyclic and ratcheting responses of UHMWPE. Kinematic stress is the main state variable in constitutive models which affect cyclic behavior and the ratcheting. Therefore, different kinematic hardening laws such as Prager, Frederick-Armstrong, Burlet-Cailletaud, Ohno-Wang and Chaboche, are used to investigate ratcheting behavior of UHMWPE. The experimental and VBO simulated responses are compared to demonstrate the current state of the simulations and future model development needs.
Keywords: UHMWPE; biaxial and uniaxial cyclic loading; ratcheting; OVERSTRESS; Engineering; Materials Science